Arbeitskleidung (1930er Jahre)
Wirtschaft;Industrie;Textil- und Lederindustrie;Textilindustrie;Bekleidungsindustrie;Kleidung Wirtschaft;Beschäftigung und Arbeit;Arbeitsmarkt (allgemein);sozio-berufliche Gruppe;Arbeiter/in